2010
DOI: 10.4103/0019-5413.67122
|View full text |Cite
|
Sign up to set email alerts
|

Primary hemiarthroplasty for unstable osteoporotic intertrochanteric fractures in the elderly: A retrospective case series

Abstract: Background:The management of unstable osteoporotic intertrochantric fractures in elderly is challenging because of difficult anatomical reduction, poor bone quality, and sometimes a need to protect the fracture from stresses of weight bearing. Internal fixation in these cases usually involves prolonged bed rest or limited ambulation, to prevent implant failure secondary to osteoporosis. This might result in higher chances of complications like pulmonary embolism, deep vein thrombosis, pneumonia, and decubitus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 57 publications
11
44
3
Order By: Relevance
“…Some studies reported that hip arthroplasty in treating these fractures had more advantages than internal fixations [4], [16], [17], [18], [19]. However, the findings of the present study did not support hemiarthroplasty as a preferred choice when compared with PFNA.…”
Section: Discussioncontrasting
confidence: 87%
“…Some studies reported that hip arthroplasty in treating these fractures had more advantages than internal fixations [4], [16], [17], [18], [19]. However, the findings of the present study did not support hemiarthroplasty as a preferred choice when compared with PFNA.…”
Section: Discussioncontrasting
confidence: 87%
“…However, the indications for such a procedure are not yet well defined: one major indication might be a comminuted and unstable pertrochanteric fracture in an elderly and debilitated patient with osteopenic or osteoporotic bone [2, 3, 5, 17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown a higher rate of complications in patients treated with osteosynthesis when compared to arthroplasty, leading to more application of arthroplasty techniques [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KH Sancheti et al 16 retrospectively analyzed 37 cases of primary hemiarthroplasty done for elderly, osteoporotic, unstable IT fractures and 91% had excellent to fair functional results.…”
Section: Discussionmentioning
confidence: 99%